1980
DOI: 10.1111/j.1600-0528.1980.tb01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supervised daily dental plaque removal by children after 3 years

Abstract: The benefits of a school-based plaque removal program are presented. Children in grades 5-8 were inclined in a study which was designed to determine the effect on oral hygiene, gingival inflammation and dental caries of removing dental plaque through supervised daily flossing and toothbrushing in school. A fluoride-free dentifrice was used. Controls did not receive instruction in plaque removal procedures nor did they engage in plaque removal activities at school. For three school years the students in the tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 11 publications
0
28
1
1
Order By: Relevance
“…The results of this study are not in agreement with the classical study of Horowitz et al (10), where they tested the effect of supervised daily tooth brushing on oral health in children. They found no statistically significant difference in dental or periodontal health among children in the study and control groups after three years.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study are not in agreement with the classical study of Horowitz et al (10), where they tested the effect of supervised daily tooth brushing on oral health in children. They found no statistically significant difference in dental or periodontal health among children in the study and control groups after three years.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 984 unique citations from 3 sources were identified (Figure ). Thirteen references of interest were identified for full‐text review, which included 12 published articles and one abstract for which we obtained the NIH grant report . After full‐text review, three randomised trials were included (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Three randomised trials on 743 participants were identified (Table ); two trials were conducted in the United States (US), and one in the United Kingdom (UK) . The enrolled participants were girls aged 11 and 12, and boys and girls aged 10 and 13, and 12 and 13 . All three trials reported DMFS scores; two trials continued for 3 years and one trial for 29 months .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations